1957
DOI: 10.1099/00221287-16-3-572
|View full text |Cite
|
Sign up to set email alerts
|

The Production of Gram-positive Variants by Azotobacter chroococcum

Abstract: SUMMARY : Cultures of Axotobacter chroococcum isolated by four independent operators regularly produced Gram-positive forms, from which typical cultures of A. chroococcum were recovered under controlled conditions. This observation appears to confirm those of earlier workers, and is in accordance with the theory that the aerobic and anaerobic nitrogen-fixing bacteria may be closely related.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

1962
1962
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
2
0
1
Order By: Relevance
“…Gambar 2 dan 3 menunjukkan bahwa sel terlihat berupa Gram-positif dan bentuknya ada yang batang (basil) maupun bulat (coccus). Hal ini menunjukkan adanya ketersesuaian dengan literatur (10), (11) yang menyatakan bahwa genus Azotobacter umumnya berbentuk variatif dari basil hingga bulat. (13) .…”
Section: Pengamatan Mikroskopis Sel Padaunclassified
“…Gambar 2 dan 3 menunjukkan bahwa sel terlihat berupa Gram-positif dan bentuknya ada yang batang (basil) maupun bulat (coccus). Hal ini menunjukkan adanya ketersesuaian dengan literatur (10), (11) yang menyatakan bahwa genus Azotobacter umumnya berbentuk variatif dari basil hingga bulat. (13) .…”
Section: Pengamatan Mikroskopis Sel Padaunclassified
“…In the Azotobacteraceae this tendency is so great that it is, in the final analysis, difficult to ascertain the typical morphology of these organisms (12). Lohnis and Smith (8), Bisset and Hale (1), Bisset et al (2), Winogradsky (16), and Vela et al ( 13) have shown that there are many morphological variations in azotobacter cultures known to be pure, or even in those said to be clonal. Indeed, Lohnis and Smith (8) and, more recently, Bisset and Hale (1) claimed that morphological variation in pure culture represents complex life cycles of the organism, including large nonsporeforming rods, coccoid budding cells, dwarf cells, giant cells, branching cells, gram-negative rods, grampositive rods, arthrospores, cysts, microcysts, gonidia, and spores.…”
mentioning
confidence: 99%
“…Indeed, Lohnis and Smith (8) and, more recently, Bisset and Hale (1) claimed that morphological variation in pure culture represents complex life cycles of the organism, including large nonsporeforming rods, coccoid budding cells, dwarf cells, giant cells, branching cells, gram-negative rods, grampositive rods, arthrospores, cysts, microcysts, gonidia, and spores. Although claims of morphological variation of this magnitude have been largely negated (7), it is still an unexplained fact that a single clone of Azotobacter vinelandii will yield at least several morphological types (2,9). The nature of this variation has not been examined adequately and, consequently, the nature of the "true" or characteristic morphology of the azotobacter has not been described definitively.…”
mentioning
confidence: 99%